2014
DOI: 10.26443/ijwpc.v1i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Humanizing clinical dentistry through a person-centred model

Abstract: Humanizing clinical dentistry through a person-centred model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 107 publications
(74 reference statements)
3
36
0
1
Order By: Relevance
“…During the training, we posited that caring for people living in poverty might include discovering and taking into account their social context. This notion is consistent with most definitions and models of person centered care [ 22 , 34 ], an approach that is gaining ground in dentistry [ 35 ]. Yet in response to strategies designed to gain knowledge of a patient’s social context, several participants raise objections that translate a generalized and predominately biomedical orientation to patient care: My business is their mouth and teeth.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…During the training, we posited that caring for people living in poverty might include discovering and taking into account their social context. This notion is consistent with most definitions and models of person centered care [ 22 , 34 ], an approach that is gaining ground in dentistry [ 35 ]. Yet in response to strategies designed to gain knowledge of a patient’s social context, several participants raise objections that translate a generalized and predominately biomedical orientation to patient care: My business is their mouth and teeth.…”
Section: Resultssupporting
confidence: 77%
“…Lack of choice and capacity—whether due to budget, time or psychosocial constraints—to follow professional recommendations will not be properly understood, empathized with, nor taken into consideration, unless addressed within a broader frame of reference. Patient centered care models represent a pertinent alternative because they advocate for a bio-psycho-social understanding of the patient as well as for discovering the meaning the latter ascribes to his or her oral health care issue, within the context of his or her life [ 22 , 34 , 35 ]. These are indeed keys to sensitive, trust-building, and relevant healthcare for low-income patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as many suggest [ 33 35 ], we recommend reinforcing dentists’ sensitivity to the situation of people on social assistance through the development of educational academic programs. We believe that “patient-centred” [ 36 ] and “social competency” approaches, for instance, can help professionals to better understand the perspectives of people living in poverty. These would facilitate the organisation of appointments by identifying appropriate time periods and avoiding the planning of patients’ unwanted visits.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, always following the PCC principles, and among them the dentist-as-person concept [4,10], we also hypothesize that adding some WIDENESS timeslots into professional agendas could result in better working conditions for dentists. It has been shown that dentists have to deal with many significant stressors in their professional lives [33].…”
Section: Interpretation and Implicationsmentioning
confidence: 98%
“…Among various improvement avenues, the organization of the dental work force should evolve with changing perceptions of individuals regarding health in modern societies. In dentistry-as in medicine-there is a trend toward person-centered care (PCC) [4], reflecting the wishes of individuals to have more power and control in their health decisions [5]. Patient-centeredness (a close relative concept to person-centeredness) is now strongly encouraged by various institutions, such as the Commission on Dental Accreditation in the United States [6], the Association of Canadian Faculties of Dentistry [7], or the Association for Dental Education in Europe [8].…”
Section: Introductionmentioning
confidence: 99%